Brown manuring effects on soil and yield of rice (Oryza sativa) under rainfed midland farming system - PRADHAN, ADIKANT; CHANDRAKAR, T; DIXIT, ANIL; KERKETTA, A K (The Indian Journal of Agricultural Sciences, 2020)
The present study conducted in the year of 2015, 2016 and 2017 aiming to determine the effect of brown manuring on rice (Oryza sativa L.) in inceptisol under midland farming of southern Chhattisgarh. Six treatment combinations with the objective of reducing chemical fertilizers, which were line sowing of rice and broadcasting dhaincha, line sowing of rice and dhaincha together in same row, incorporation of dhaincha in line sown rice at 30 DAS, broadcasting of rice and dhaincha, line sowing of rice and broadcasting of rice, all dhaincha crops were smothered by spraying 2,4-D at 25 DAS. The higher grain yield was with Line sowing of rice and dhaincha together in same row followed by line sowing of rice and broadcasting dhaincha and 30.95% higher grain yield in Line sowing of rice and dhaincha together in same row over broadcasting of rice. Soil organic carbon showed an overall increase over the initial SOC of 0.28%. The mean SOC (%) was 0.62, 0.45 and 0.41 % higher under line sowing of rice and dhaincha together in same row, line sowing of rice and broadcasting dhaincha and incorporation of dhaincha in line sown rice at 30 DAS treatments respectively over the broadcasting of rice. The highest B:C was under Line sowing of rice and dhaincha together in same row (4.26) then incorporation of dhaincha in line sown rice at 30 DAS (2.37) followed by broadcasting of rice and dhaincha line sowing of rice 2.39, 2.86 and 2.46, respectively.